Taxonomy of Epictia munoai (Orejas-Miranda, 1961) (Squamata: Serpentes: Leptotyphlopidae) - Francisco, Bárbara Cristina S.; Pinto, Roberta R.; Fernandes, Daniel S. (Zootaxa, 2012)
The wormsnakes Leptotyphlopidae include the smallest and thinnest snakes of the world. This group has historically fewtaxonomic studies and the descriptions of taxa in general are superficial, frequently preventing an accurate identification.This family includes the genus Epictia with many representatives with taxonomic major issues, including Epictia munoai.We redescribe and compare E. munoai with other related cisandine species in order to evaluate its taxonomic status con-sidering the morphological analysis of specimens. A table with some diagnostic characters of each species is presented.Epictia munoai is distinguished from other related species mostly by low number of middorsal and midventral scales, and is distributed in coastal areas in southern Brazil, Uruguay and northeastern Argentina.